The real exchange rate-foreign direct investment controversy in South Africa: an application of ARDL approach - Dahir, Ahmed Mohamed; Mahat, Fauziah; Amin Noordin, Bany Ariffin; Ab Razak, Nazrul Hisyam (Canadian Center of Science and Education, 2017)
This paper examines the relationship between real exchange rate and foreign direct investment. We apply autoregressive distributed lag (ARDL) bounds testing method to estimate short and long-run relationships between the series in South Africa over the period of 1987-2016. The results reveal long-run cointegration relationships among variables are confirmed, implying real exchange rate, domestic market size stimulate the foreign direct investment in the long run. Furthermore, there is significant Granger unidirectional causality foreign direct investment to real exchange rate in short and long run and from market size to trade openness in a short run. This finding further suggests that the exchange rate instability are likely to be substantially harmful to a positive effect of FDI and should be avoided in South Africa.